2013
DOI: 10.1002/aoc.3024
|View full text |Cite
|
Sign up to set email alerts
|

Template‐less synthesis of polymer hollow spheres: an efficient catalyst for Suzuki coupling reaction

Abstract: We report here a method for the preparation of polymer hollow spheres in which 3-aminoquinoline (3-AQ) and palladium acetate were used as precursors. During the reaction 3-AQ was oxidized and formed poly(3-AQ). IR and Raman spectra provided information on the chemical structure of the polymer. The oxidation state of palladium was confirmed by X-ray photoelectron spectroscopic analysis. Transmission and scanning electron microscopy were used to determine the size and morphology of the polymer. The palladium-pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 46 publications
1
10
2
Order By: Relevance
“…Irregular shaped, heterogeneous and micro-sized platelike structures were observed from this Figure. EDX analysis assigned the existence of copper, carbon, nitrogen and sulfur atoms on the surface of the product (Figure 3). This morphology is different from previous studies [6,7,9]. The thickness and the length of rods observed at Figure 4 were around 200-400 nm, 4-6µm, respectively.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Irregular shaped, heterogeneous and micro-sized platelike structures were observed from this Figure. EDX analysis assigned the existence of copper, carbon, nitrogen and sulfur atoms on the surface of the product (Figure 3). This morphology is different from previous studies [6,7,9]. The thickness and the length of rods observed at Figure 4 were around 200-400 nm, 4-6µm, respectively.…”
Section: Resultscontrasting
confidence: 99%
“…The characteristic benzenoid and quinoid vibrations were observed at 1619 and 1511 cm -1 . The peak at 1275 cm -1 was also observed possibly due to C-N stretching vibration [7]. In addition, the peak observed at 1373 cm -1 with medium intensity was assigned to C-N stretching for quinoid ring and harmony with literature [7].…”
Section: Resultssupporting
confidence: 55%
“…In association with our ongoing research on the development of effective catalysts for synthetic organic transformations,25, 26, 2833 we have found that a polypyrrole‐immobilised Pd nanoparticle catalyst can be used for the chemoselective transfer hydrogenation of α,β‐unsaturated carbonyls in the presence of NH 4 OOCH or HCOOH under reflux conditions. The interesting aspect of this catalyst is that it can selectively hydrogenate the olefins or acetylenes without affecting the carbonyl moiety and ArX (X=Cl, Br) bonds with an excellent yield of products for a wide range of substrates.…”
Section: Introductionmentioning
confidence: 92%
“…The polymer matrix serves both as the support as well as the stabiliser of the nanoparticles, which provides a mechanism to prevent aggregation. Pd‐based catalysts, in particular nano‐sized Pd particles, have recently drawn a great deal of attention because of their versatile role in organic synthesis 2833. Pd‐catalysed hydrogenation reactions are important for industrial applications 3436.…”
Section: Introductionmentioning
confidence: 99%
“…Such composite architecture shows various properties directly relevant and of benefit to energy storage [9] and catalytic activity [10][11][12][13][14][15][16]. Nanoparticles, such as gold and silver, with the unique optical property and the sizedependent electrochemistry have made them the ideal system of choice in the area of sensor application for biomolecule recognition.…”
Section: Introductionmentioning
confidence: 99%